FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI DI DINAS KEBUDAYAAN DAN PARIWISATA KOTA PEKANBARU - Muhammad Hendrico; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this research is to know how the factors that influence performance of Dinas Kebudayaan dan Pariwisata Kota Pekanbaru employees and what is the most dominant factor that influence performance of Dinas Kebudayaan dan Pariwisata Kota Pekanbaru employees.This research used descriptive qualitative method to analyze the problem. The sample of this research are consist of 40 respondents. Then, the data collected by observation, interview and questionnaire. By using likert scale as the counting appliance to decided the length of intervals.Based on the result of the research, there are three factors that influence performance of Dinas Kebudayaan dan Pariwisata Kota Pekanbaru employees, they are internal factor employee, a factor internal organization and external factors organization. Factor that most dominant was internal factors organization from the indicator working climate, and internal factor employee from the indicator competences and external factors organization with indicators culture and religion. According to the response respondents indicators knowledge (education), political life, and social life less influence their performance.Keywords : human resources, performance, factors that influence the employees performance